Improving Customer Satisfaction Through the Role of Mediation Word of Mouth Case Study at Mcdonald's Cut Meutia Bekasi - Mohammad Dandy Kurniawan; Parlagutan Silitonga (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This . study aims to analyze and determine the effect of product quality and brand image on customer satisfaction through word of mouth mediation at McDonald's Cut Meutia Bekasi. Respondents in this study were McDonald's customers who had visited at least 2 times and bought McDonald's food products. This sampling technique is purposive sampling with a total of 150 respondents. The analytical method used is descriptive and quantitative methods. The results of this study indicate that product quality and brand image have a significant effect on customer satisfaction, product quality and brand image have a significant effect on word of mouth, word of mouth has a significant effect on customer satisfaction and there is an indirect effect on product quality and brand image on customer satisfaction through word of mouth has a significant effect.